Fight or flight: the importance of team work, leadership and human governance - Tee, Keng Kok; Tiong, Hooi Gi; Chong, Chiao Wei; Ng, Siew Imm (Universiti Putra Malaysia Press, 2013)
This case discusses issues revolving around organization behavior within MAB & Co., a pharmaceutical company in Malaysia. The company experienced substantial staff turnover following the announcement of its acquisition by Marck. The issue was further aggravated with the resignation of the Senior Manager of the Research & Development (R&D) division, who had served the company for 10 years. The previous Manager of the Marketing division was then promoted to the vacancy. However, the new appointment was not well-received by the existing staff, and hence conflicts started to surface. This case highlights the potential organization structural change arising from the impending merger exercise, coupled with deteriorating employee morale as evidenced by increasing staff turnover, which could eventually lead to disorganization of the company.